Effects of cardiopulmonary resuscitation with automated external defibrillator training among schoolchildren in Slovenia: A pre- and post-test cohort study - Pivač Sanela; Skela-Savič Brigita; Gradišek Primož (Sciendo, 2021)
A low proportion of bystanders in Slovenia are willing to provide resuscitation to people experiencing cardiac arrest. We measured knowledge acquired after cardiopulmonary resuscitation training among Slovenian children in the final three grades of primary school.